The 48 laws of power - Greene, Robert; Elffers, Joost (New York : Penguin Books, 2000)
Amoral, cunning, ruthless, and instructive, this piercing work distills three thousand years of the history of power into 48 well-explicated laws. It outlines the laws of power in their unvarnished essence, synthesizing the philosophies of Machiavelli, Sun-tzu, Carl von Clausewitz, and other great thinkers. Some laws teach the need for prudence, the virtue of stealth, and many demand the total absence of mercy, but like it or not, all have applications in real life. Illustrated through the tactics of Queen Elizabeth I, Henry Kissinger, P. T. Barnum, and other famous figures who have wielded--or been victimized by--power, these laws will fascinate any reader interested in gaining, observing, or defending against ultimate control.--From publisher description.
Includes bibliographical references (p. 431-432) and index.
All age.
Keywords: Power (Philosophy).; Control (Psychology).; Pouvoir (Morale).; Contr?ole (Psychologie).